2007
DOI: 10.1038/sj.bjc.6603693
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of HPV18 to cervical cancer is underestimated using high-grade CIN as a measure of screening efficiency

Abstract: In one geographical area, 14 high-risk human papillomavirus types in cervical intraepithelial neoplasia (CIN2/3; n =139) and cervical squamous cell carcinoma (SCC; n =84) were analysed. HPV18 was more prevalent in SCC than CIN2/3 (OR 9.8; 95% confidence interval: 2.5–39). Other high-risk types prevalences corresponded in CIN2/3 and SCC. Evaluations using CIN2/3 as a measure of efficiency underestimate the contribution of HPV18 to SCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…On the other hand, HPV18 is rarely reported to be present at the same time as high-grade CIN is diagnosed (43)(44)(45). In an attempt to explain this paradox, it has been suggested that HPV18-associated disease rapidly progresses through the preinvasive stages of cervical neoplasia (42).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, HPV18 is rarely reported to be present at the same time as high-grade CIN is diagnosed (43)(44)(45). In an attempt to explain this paradox, it has been suggested that HPV18-associated disease rapidly progresses through the preinvasive stages of cervical neoplasia (42).…”
Section: Discussionmentioning
confidence: 99%
“…In these patients, HPVs 16, 52, and 58 were the three most frequently observed HPV types. Because HPV 18 is the second most frequently observed HPV genotype in cervical cancer [35], in this study, we focused on HPVs 16, 52, 58, and 18. , and 58 were classified as "other hrHPVs." Patients who were not infected with any hrHPVs were referred to as "no hrHPVs" patients.…”
Section: Patientsmentioning
confidence: 99%
“…Cytological and histological results were combined to classify the results into the following diagnoses: normal, CIN1, CIN2, CIN3, and cervical cancer. HPVs 16,18,31,33,35,39,45,51,52,56,58,59, and 68 were classified as hrHPVs. Of these, HPV 16, 18, 52, and 58 were categorized separately.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…24,25,33,34 Progression probabilities from CIN1 to CIN3 and from CIN3 to cancer were type-specific. 5,19,27 The progression rate from HPV infection to CIN3 was age-dependent and assumed to be 2.5-fold higher above the age 30 than at young age. 35 The progression from CIN3 to cervical cancer was calibrated on registry data (www.ikcnet.nl) and on historical data.…”
mentioning
confidence: 99%